The Effect of Work Discipline and Work Motivation on Employee Performance at Dpmptsp Makassar City - Andi Mutmainnah A; M. Ikhwan Maulana Haeruddin; Anwar (PT. Maju Malaqbi Makkarana, 2026)
This study aims to test and analyze the influence of work compliance and work motivation on the work results of apparatus at the Makassar Regional Investment and One-Stop Integrated Services Office. The background of this study is based on the importance of improving the performance of the apparatus in providing effective, responsive, and quality public services. Work compliance is seen as the attitude of the apparatus in obeying applicable rules, procedures, discipline, and work standards, while work motivation reflects the motivation, enthusiasm, and willingness of the apparatus to complete tasks. The population in this study is all apparatus in the agency, with a sample of 59 respondents. Data were collected through questionnaires and analyzed using multiple linear regression techniques with the help of SPSS software version 23.00. The results of the study show that work compliance has a positive and significant effect on the work results of the apparatus. This means that the higher the level of compliance of the apparatus with work rules and procedures, the better the work results achieved. Meanwhile, work encouragement has a positive but insignificant effect on the work results of the apparatus. These findings show that work motivation needs to be supported by a conducive work system, supervision, and organizational environment in order to be able to improve performance optimally. The implication is that agencies need to strengthen the culture of discipline and design a more targeted motivation strategy according to the needs of public service apparatus in a sustainable manner in the region